Design Web-Based Registration And Data Management Of Student Thesis Information System - Rosiyati MH Thamrin; Rian Andriani (STMIK PONTIANAK, 2021)
The thesis data management process at STIMIK Sepuluh Nopember Jayapura currently still uses Microsoft Excel, so the processing takes a lot of time, another obstacle that arises is the title submission process, where students have to come to campus to submit titles then announcements still use the announcement board so that students who want to get the information must go to the STIMIK Sepuluh Nopember campus. The purpose of making the system is to solve the above problems and at the same time make it easier for students in the process of submitting titles. The design of this system uses the waterfall method, while the data collection method uses several methods such as observation, interviews and literature study. For web development using the PHP programming language. The final result of this design is a web that can be used by students to submit titles, see a list of thesis titles that have been taken and so on. While the output from the web that is made is a list of student thesis titles STIMIK Sepuluh Nopember Jayapura and announcements such as approval of titles submitted, supervisors, examiners and payment issues.